Magnetoelectricity in the ferrimagnetic Cu2OSeO3:symmetry analysis and Raman scattering study - Gnezdilov, V.P.; Lamonova, K.V.; Pashkevich, Yu.G.; Lemmens, P.; Berger, H.; Bussy, F.; Gnatchenko, S.L. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
We report Raman scattering studies and magneto/structural symmetry analysis of the many sublattices ferrimagnet Cu2OSeO3 with a cubic symmetry and a linear magnetoelectric effect. There is no spectroscopic evidence for structural lattice distortions below TC = 60 K, which are expected due to magnetoelectric coupling. Using symmetry arguments we explain this observation by considering a special type of ferrimagnetic ground state which does not generate a spontaneous electric polarization. Interestingly, Raman scattering shows a strong increase of electric polarization of media through a dynamic magnetoelectric effect as a remarkable enhancement of the scattering intensity below TC. New lines of purely magnetic origin have been detected in the magnetically ordered state. A part of them are attributed as scattering on exchange magnons. Using this observation and further symmetryconsiderations we argue for strong Dzyaloshinskii–Moriya interaction existing in the Cu2OSeO3.